Descending Aortic Translocation and Right Pulmonary Artery Reimplantation for Midline Descending Aorta and Crossed Pulmonary Arteries in an Infant. Issue 1 (January 2019) - Mongé, Michael C.; Hauck, Amanda L.; Popescu, Andrada R.; Forbess, Joseph M.; Backer, Carl L.
Left mainstem bronchial compression by a midline descending thoracic aorta is a rare anatomic variant. Translocation of the descending thoracic aorta to the ascending aorta has recently been described to treat this condition. We performed an aortic translocation and right pulmonary artery reimplantation in a 4-month-old infant with severe pulmonary hypertension secondary to right pulmonary artery stenosis and left bronchial compression by a midline descending thoracic aorta. The procedure was successful in ameliorating the patient's left mainstem bronchial compression and pulmonary hypertension. Descending aortic translocation should be considered when the left bronchus is compressed causing respiratory symptoms.